Thorough Investigation of the Phenolic Profile of Reputable Greek Honey Varieties: Varietal Discrimination and Floral Markers Identification Using Liquid Chromatography-High-Resolution Mass Spectrometry - Koulis, Georgios A; Tsagkaris, Aristeidis S; Katsianou, Panagiota A; Gialouris, Panagiotis-Loukas P; Martakos, Ioannis; Stergiou, Fotis; Fiore, Alberto; Panagopoulou, Eleni I; Karabournioti, Sofia; Baessmann, Carsten; van der Borg, Noud; Dasenaki, Marilena E; et al. (Molecules (Basel, Switzerland), 2022)
Honey is a highly consumed commodity due to its potential health benefits upon certain consumption, resulting in a high market price. This fact indicates the need to protect honey from fraudulent acts by delivering comprehensive analytical methodologies. In this study, targeted, suspect and non-targeted metabolomic workflows were applied to identify botanical origin markers of Greek honey. Blossom honey samples (n = 62) and the unifloral fir (n = 10), oak (n = 24), pine (n = 39) and thyme (n = 34) honeys were analyzed using an ultra-high-performance liquid chromatography hybrid quadrupole time-of-flight mass spectrometry (UHPLC-q-TOF-MS) system. Several potential authenticity markers were revealed from the application of different metabolomic workflows. In detail, based on quantitative targeted analysis, three blossom honey markers were found, namely, galangin, pinocembrin and chrysin, while gallic acid concentration was found to be significantly higher in oak honey. Using suspect screening workflow, 12 additional bioactive compounds were identified and semi-quantified, achieving comprehensive metabolomic honey characterization. Lastly, by combining non-targeted screening with advanced chemometrics, it was possible to discriminate thyme from blossom honey and develop binary discriminatory models with high predictive power. In conclusion, a holistic approach to assessing the botanical origin of Greek honey is presented, highlighting the complementarity of the three applied metabolomic approaches.
Keywords: Chromatography, High Pressure Liquid; Chromatography, Liquid; phenolic compounds; botanical origin; Honey; authenticity; discrimination; Thymus (rostlina); Greek honey; fenoly; Biomarkers; high-resolution mass spectrometry; honey; Řecko; biologické markery; chromatografie kapalinová; Greece; metabolomics; Phenols; Thymus Plant; chemometrics; hmotnostní spektrometrie; vysokoúčinná kapalinová chromatografie; Mass Spectrometry; med